INOVASI PENGEMBANGAN KURIKULUM PENDIDIKAN DALAM PERSPEKTIF KURIKULUM HUMANISTIK - Nurut Taufik (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
The curriculum is an important instrument in the implementation of education, without the educational curriculum it will be unclear its direction and purpose. Innovation in curriculum development is very important in the development of learning, seeing its dynamic nature is always changing. The purpose of this study is to determine the innovation of educational curriculum development and at the same time try to analyze the character of the curriculum development innovation through a humanistic curriculum approach. This type of research is qualitative with a case study type of research. Data collection techniques are carried out using interviews, observation and documentation. Data analysis is carried out through the stages of data reduction, data display, and verification and conclusions. Data validity tests are carried out using the triangulation method. The results showed that the educational curriculum development innovation developed by MI Darul Hikmah has several humanistic curriculum characters as explained by the informants. In terms of innovation, the development of educational curriculum in MI Darul Hikmah has the principle of balance, namely success in the world and the hereafter, the form of curriculum innovation developed by the school is memorization of suras, reading and writing iqra / al-qur'an and so on.